Effect of incorporating rice bran or parboiled rice polish with or without exogenous phytase in the diet on growth of Jinding ducklings - Pal, Nebash Chandra; Bulbul, Syed Mohammad; Mawa, Zannatul; Ahammad, Muslah Uddin (Research in Agriculture Livestock and Fisheries, 2015)
A total of 48 straight-run day old ducklings (DOD) of Jinding were fed ad libitum on four (4) iso-nitrogenous and iso-caloric diets (3000 Kcal ME/kg and 22% CP) having 3 replicates each. The diets were formulated using 20% rice bran (RB) or parboiled rice polish (PRP) with or without exogenous phytase (10g/kg). Ducklings were fed up to 28 days of age to observe the effect of RB and PRP based diet on the growth performance. Feeding of PRP based diet with enzyme resulted in increased live weight gain and feed efficiency. There was no difference in feed intake on both diets (p>0.05). However, the formulating cost of PRP based diet was higher than that of RB based diet. Addition of enzyme promoted growth and feed efficiency but did not affect feed intake significantly during the experimental period and increased feed cost. Therefore, it appeared that the biological performance of PRP based diet with or without enzyme was better than that of RB based diet. However, the feed cost was less in RB based diet with or without phytase. Therefore, to formulate low cost diet, RB seemed to be superior over PRP, but for better growth performance PRP can be used in the diet of ducklings. In conclusion, the findings demonstrated that the PRP based diets with or without phytase was superior to RB based diets with or without phytase in terms of growth performance, but RB based diet was superior in terms of feed cost. Therefore, it appeared that increased growth performance cannot be a basis of using RB and PRP. Rather, costeffectiveness of feeding ducklings on RB and PRP based diet must be taken into account. Res. Agric., Livest. Fish.2(3): 445-451, December 2015